THE OPPORTUNITY OF PROFIT SHARING SCHEME IMPLEMENTATION ON MONEYLENDER IN EXPANDING ISLAMIC BANKING SERVICE, EVIDENCE FROM TRADITIONAL MARKET IN SURABAYA, INDONESIA - Agni Alam Awirya; Komalia Rahmayani (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2012)
This research dealt with microeconomics finance that focused on the opportunity to implement profit sharing design on moneylenders in order to develop the principles of Islamic banking service. The method of this research was using descriptive analysis and logistic regression that was applied to two kinds of respondents; namely, Moneylenders as the fund owner and Customer as the fund user in the traditional market in Surabaya, Indonesia. The result showed that moneylenders agree to use profit sharing design more than their customer. This finding could be used as a good opportunity for Islamic banking to apply its principles into traditional markets. There were some variables which influence moneylenders to agree with the design of profit sharing, they were: initial capital and the number of customer with positive direction and the number of dependents with negative direction. On the other hand, variables that influence customer to agree with profit sharing scheme were initial capital, turnover and the understanding of profit sharing scheme with positive direction and age with negative direction.